Fostering Excellence in Madrasah through Collaborative Supervision: A Management Perspective - Misbah, Misbah; Aziz, Abd.; Sokip, Sokip; Kojin, Kojin (International Journal of Science, Technology & Management, 2024)
This research is motivated by the lack of collaborative guidance among some members of the madrasah and the supervisor, which hinders the improvement of the quality of a madrasah institution. Therefore, it is necessary to establish collaboration or synergy among the head of the madrasah, the madrasah committee, several teachers, and the supervisor in advancing the quality of the madrasah. This research employs a qualitative approach with a multi-site study design. Data collection techniques include in-depth interviews, participant observation, and documentation. Data analysis uses single-case analysis and cross-case analysis. Data validity techniques involve credibility, transferability, dependability, and confirmability.The research findings indicate that: (1) the collaboration between supervisors and heads of madrasahs in formulating plans (planning) to improve the quality of the institution includes: a) formulating and developing the vision, mission, and goals of the madrasah; b) preparing the Mid-Term Work Plan (RKJM), the Madrasah Work and Budget Plan (RKAM), and the Annual Work Plan (RKT); c) conducting workshops and training for teachers and institutional staff; d) developing madrasah management systems and information technology and PBM (Self-Learning Platform); and e) preparing KTSP/Merdeka curriculum; (2) the collaboration between supervisors and heads of madrasahs in implementing the process (actuating) to improve the quality of the institution involves: a) organizing guidance, workshops, and training for madrasah teachers; b) providing support and guidance for all programs within the institution; c) developing a madrasah curriculum tailored to the institution's situation and conditions; d) producing works/products or learning journals, and developing an excellent KTSP madrasah curriculum.